2020
DOI: 10.1088/2053-1591/ab945a
|View full text |Cite
|
Sign up to set email alerts
|

New deposition method of MgB2 thin film with thermal evaporation of Mg and sputtering of B

Abstract: We are now developing a new in situ deposition process for MgB 2 film as a candidate method to massproduce MgB 2 thin film superconducting tape. In the new method, a MgB 2 film is deposited on a heated metal substrate by a hybrid deposition method, which consists of thermal evaporation of magnesium and sputtering of boron. By using the hybrid deposition method, the substrate temperature can raise from 250 to 350°C, while its fluctuation is kept less than 1°C, which will improve the quality and reproducibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…It is necessary to develop a deposition technique suitable for incorporation in a reel-to-reel machine that is used for the synthesis of long MgB 2 -thin-film superconducting tapes. 17) The synthesis process for these machines involves the deposition of magnesium and boron on a heated long-tape substrate passed between the reels while taking up the substrate by the reels. Here, several magnesium and boron evaporation sources are arranged in line or in a matrix.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is necessary to develop a deposition technique suitable for incorporation in a reel-to-reel machine that is used for the synthesis of long MgB 2 -thin-film superconducting tapes. 17) The synthesis process for these machines involves the deposition of magnesium and boron on a heated long-tape substrate passed between the reels while taking up the substrate by the reels. Here, several magnesium and boron evaporation sources are arranged in line or in a matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The technique comprises the thermal evaporation of magnesium and sputtering of boron. 17) The J c of the MgB 2 film deposited via this technique was 31 000 A mm −2 at 20 K under a self-field (0 T). However, the MgB 2 film exhibited a low J c of 380 A mm −2 at 20 K under a magnetic field of 1 T applied parallel to the film, and it is necessary to significantly increase the obtained J c under these conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The reliability of thermal evaporation of Mg is supported by other studies focusing on the coevaporation of Mg and B to form MgB thin films. 32,33 These considerations make thermal coevaporation of said constituents a promising technique to fabricate Mg x Bi y thin films.…”
mentioning
confidence: 99%
“…However, already in 1979 Long et al had reported on the thermal coevaporation of Mg and Bi and the formation of a two-component alloy in which the compositional variations were below 0.5% . The reliability of thermal evaporation of Mg is supported by other studies focusing on the coevaporation of Mg and B to form MgB thin films. , These considerations make thermal coevaporation of said constituents a promising technique to fabricate Mg x Bi y thin films.…”
mentioning
confidence: 99%